Estudio de factibilidad para la creación de un gimnasio, en el barrio los Alpes municipio de corozal – Departamento de Sucre (2022)
In this document, a feasibility study was carried out to determine the feasibility of creating a gym in the Los Alpes, municipality of Corozal, Department of Sucre, for which a market analysis was carried out to determine the level of acceptance of the project. the characteristics of the demand, and the way in which the business is marketed, likewise, a technical analysis was carried out that includes the physical, administrative and operational aspects of the creation of the gym. On the other hand, the organizational scope allows establishing an administrative structure with respect to the organization chart that the project requires for its operation, and in the financial component, the main financial statements were presented, such as income statement, statement of financial position, cash flow that they reflect the entity's cost structure, projection of sales, income and expenses. Finally, a financial analysis is carried out by means of financial indicators such as the net present value, the internal rate of return, the cost-benefit ratio and the capital recovery time; whose results allowed to determine the financial viability of the project, yielding favorable results in financial terms for its implementation, in the municipality of Corozal-Sucre